Phosphodiesterase-induced cAMP degradation restricts hepatitis B virus infection. - Evripioti, Antonia Alexandra; Ortega-Prieto, Ana María; Skelton, Jessica Katy; Bazot, Quentin; Dorner, Marcus (The Royal Society, 2019)
Hepatitis B virus (HBV) entry into hepatocytes is mediated via a high-affinity interaction between the preS1 glycoprotein and sodium/bile acid cotransporting polypeptide (NTCP). To date, in vitro model systems rely on high multiplicities of infection to achieve infection of cell lines overexpressing human NTCP. This study investigates a novel regulatory pathway for NTCP trafficking to the cell surface, induced by DMSO-mediated cellular differentiation. DMSO rapidly induces high cell surface expression of NTCP and results in increased susceptibility of cells to HBV infection. Additionally, DMSO treatment induces actin, as well as Tubulin reshaping within the cells. We show that direct disruption of the actin and Tubulin network directly enhances NTCP expression and the subsequent susceptibility of cells to HBV infection. DMSO induces these changes via alterations in the levels of cyclic (c)AMP, which participates in the observed actin rearrangements. Blocking of phosphodiesterases (PDEs), which degrade accumulated cAMP, had the same effect as DMSO differentiation and demonstrates that DMSO prevents phosphodiesterase-mediated cAMP degradation. This identifies adenylate cyclase as a novel target for blocking the entry of HBV via targeting the cell surface accumulation of NTCP. This article is part of the theme issue 'Silent cancer agents: multi-disciplinary modelling of human DNA oncoviruses'.
Keywords: Virología - Investigación; Virus de la hepatitis; Hepatitis - Tratamiento; Virology; Virus; Hepatitis